GAMBARAN PEMERIKSAAN TES CEPAT MOLEKULER (TCM) GENEXPERT PADA PASIEN DI RUMAH SAKIT UMUM DAERAH PALEMBANG BARI - Bastian Darwin (jurnal kesehatan terapan sains dan teknologi, 2024)
Background: Tuberculosis is an infectious disease caused by the bacterium Mycobacterium tuberculosis. The diagnosis of pulmonary TB is made based on the clinical picture, physical examination, radiological picture, laboratory examination, and tuberculin test. The pulmonary TB diagnosis currently used routinely in laboratories including hospitals and health centers is bacteriological diagnosis using the rapid molecular test (TCM) technique, while microscopic examination is used as a follow-up examination (monitoring) in patients receiving treatment. TCM examination is a molecular detection method based on nested real-time PCR. The use of TCM is a priority for TB testing because it has several advantages, including: it can diagnose TB and resistance to rifampicin quickly, accurately with high sensitivity, and results can be known in approximately 2 hours. Objectives: The aim of this study is to see the description of TCM examinations in patients at Palembang BARI Regional Hospital based on gender and age groups. Method: This research was conducted at the Palembang BARI Regional General Hospital Laboratory Installation. The samples taken were from patients at the Palembang BARI Regional General Hospital and not referrals from other health service facilities. 50 samples were taken and grouped based on TCM results, gender and age. Result: In grouping based on TCM results, the highest result was negative. In gender grouping, more male patients underwent TCM examinations. In the age grouping, the elderly are more likely to undergo TCM examinations. Conclusion: There are several factors that cause a person to become infected with TB, namely social status, smoking, and having the habit of drinking alcohol.